Responses of seagrass to anthropogenic and natural disturbances do not equally translate to its consumers. (23rd September 2015) - Tomas, Fiona; Martínez‐Crego, Begoña; Hernán, Gema; Santos, Rui
Abstract Coastal communities are under threat from many and often co‐occurring local (e.g., pollution, eutrophication) and global stressors (e.g., climate change), yet understanding the interactive and cumulative impacts of multiple stressors in ecosystem function is far from being accomplished. Ecological redundancy may be key for ecosystem resilience, but there are still many gaps in our understanding of interspecific differences within a functional group, particularly regarding response diversity, that is, whether members of a functional group respond equally or differently to anthropogenic stressors. Herbivores are critical in determining plant community structure and the transfer of energy up the food web. Human disturbances may alter the ecological role of herbivory by modifying the defense strategies of plants and thus the feeding patterns and performance of herbivores. We conducted a suite of experiments to examine the independent and interactive effects of anthropogenic (nutrient and CO2 additions) and natural (simulated herbivory) disturbances on a seagrass and its interaction with two common generalist consumers to understand how multiple disturbances can impact both a foundation species and a key ecological function (herbivory) and to assess the potential existence of response diversity to anthropogenic and natural changes in these systems. While all three disturbances modified seagrass defense traits, there were contrasting responses of herbivores to such plant changes. Both CO2 and nutrient additions influenced herbivore feeding behavior, yet while sea urchins preferred nutrient‐enriched seagrass tissue (regardless of other experimental treatments), isopods were deterred by these same plant tissues. In contrast, carbon enrichment deterred sea urchins and attracted isopods, while simulated herbivory only influenced isopod feeding choice. These contrasting responses of herbivores to disturbance‐induced changes in seagrass help to better understand the ecological functioning of seagrass ecosystems in the face of human disturbances and may have important implications regarding the resilience and conservation of these threatened ecosystems.